Significant contribution of Czech geobotanists to the syntaxonomic study of the vegetation of the Czech Republic (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Significant contribution of Czech geobotanists to the syntaxonomic study of the vegetation of the Czech Republic